119 Clinical Decision Support System (CDSS) on Medication-Related Fall Risk: Wishes and Needs of European Physicians. (20th December 2019) - Ploegmakers, Kim; Linn, Annemiek; Medlock, Stephanie; Van der Velde, Nathalie; Van Weert, Julia
Abstract: Background: Medication is the second most important cause of falls in older adults, after mobility impairments. Doctors struggle to withdraw Fall Risk Increasing Drugs (FRIDs). They tend to overestimate the beneficial effect of medication and underestimate the risk of side effects. With an online survey we explored if 1) European doctors want digital support during medication review of older fallers by presentation of a personalized fall risk estimation of a patient and 2) what potential barriers and facilitators exist for the use of a Clinical Decision Support System (CDSS) that communicates fall risk. Methods: We performed online surveys in 10 European countries among 359 European physicians who care for older fallers. 68% of the participants were geriatricians. Results: 88% of physicians would like to receive help with performing a medication review. Barriers for usage that were mentioned most frequently were: technical issues (74%), indicating a reason when overriding an alert (62%) and unclear advice (60%). Most important facilitators were if the system: is beneficial to patient care (75%), is user friendly (74%) and fits into the workflow (66%) Conclusion: most physicians would like to receive help from a CDSS when performing a medication review. For a successful implementation the barriers and facilitators found must be taken into account during development of the system as well as differences between countries.